EVALUATION OF SERUM LACTATE DEHYDROGENASE LEVELS IN TYPHOID FEVER. - K. SAMEERA; T. SUNITHA; NAVEEN KUMAR. P; SUJATHA. P (International Journal of Pharma and Bio Sciences, 2013)
Typhoid fever is a systemic life-threatening infection caused by the bacterium Salmonella enterica serotype Typhi occurring more frequently in underdeveloped regions of the world due to overcrowding and poor sanitation. Initiation of appropriate therapy decreases severity and clinical outcome of the disease which requires early and accurate diagnosis. Pathogenesis due to typhoid leads to various biochemical alterations. Present study was undertaken to investigate serum LDH activities in typhoid fever and to assess its clinical utility as a biochemical marker in typhoid fever. Comparison of LDH levels were also done in other fevers and healthy controls. Other parameters were also investigated viz, serum urea, serum creatinine, serum sodium and serum potassium. In the present study we observed a statistically significant increase in concentrations of LDH in typhoid fever patients when compared with other fever patients and in healthy controls. Other parameters did not exhibit any statistical significance.